الخطاب الروائي النسوي السعودي (قراءة في هوية المرأة وبناء ذاتها) - سالمي, مريم (جامعة الوادي - University of Eloued, 2022)
تمثل الرواية منعطفا تاريخيا فاصلا في حياة الشعوب، وأصبح وجودها حاجة من حاجات الإنسان؛ رغم أنها وسيلة لبلوغ الحاجة وذلك لأنها الصوت الذي بواسطته يسمع الآخرون أنين الآخرين، ومعرفة مستوى معيشتهم، أو حتى مستوى سعادتهم، وما بلغوه من رفاه. تزايد الاهتمام بالرواية النسائية خلال العقود الأخيرة بشكل عام، وفي منطقة الخليج العربي بشكل خاص، حيث ركّز النقاد على تحليل الخطاب السردي باعتباره الوسيلة التي تستخدمها الكاتبة للتعبير عن أفكارها وتوجهاتها وعرض قضاياها وموضوعاتها. تهدف هذه الدراسة إلى رصد المشهد الإبداعي النسوي في الرواية السعودية الذي بدأ ينمو شيئا فشيئا، التي انطلقت من الواقع لتعبر عنه، في محاولة للهروب من القيود والالتزامات المتداولة عبر الزمن، لتقبض على اللحظة الإبداعية الهاربة لتنتج أدبا راقيا. The novel represents a historical turning point in the lives of peoples, and its existence has become one of the human needs. Although it is a means of fulfilling a need, because it is the sound by which others hear the moaning of others, and know their standard of living, or even the level of their happiness, and the level of well-being they have attained. Interest in the women's novel has increased in recent decades in general, and in the Arab Gulf region in particular, where critics have focused on analyzing narrative discourse as the means used by the writer to express her ideas and directions and present her issues and themes. This study aims to monitor the feminist creative scene in the Saudi novel, which began to grow little by little, which started from reality to express it, in an attempt to escape from the restrictions and obligations traded through time, to catch the escaped creative moment to produce high-end literature.
مقال
Keywords: الرواية، الروائيات السعوديات، الإبداع، النسوي